Children’s play paints safety – What is the reality in Portuguese schools and at retail stores? - Rebelo, Andreia (2015)
Children’s play paints, an attractive tool for preschool activities, can be classified in artist paints (gouaches, acrylics, watercolors, fingerpaints) and face paints. These products composition is not always known since not all are required to bear their ingredients in the label packaging. The present study aimed to characterize the children’s play paints available in schools and retail stores and also to assess the practices involved in the acquisition, handling and storage of these products by schools and that may have impact on the product quality and safety. For this purpose were studied paints from 8 schools and 7 retail stores from Porto (Portugal), in a total of 17 popular brands. The results shows that the label information differs from product type, taking into account the legal requirements applied to each one (artist paints or face paints). The main hazards stated in the products label are related with the possibility of ingestion of small pieces that are part of the product. Only brands of face paints (60%) mentioned the potential risk to develop allergic reactions or skin irritation problems arising from their application. As regards to school practices, they are aware to the importance in purchasing products suitable for children use however, some of the behaviors during storage and handling of these products may affect their quality and safety.